(untitled) (Bangladesh Journal of Botany, 2023)
Duckweeds are common floating flowering plants belonging to Lemnaceae. Five main genera known as duckweed are found in tropical water bodies mostly under eutrophic condition. Despite of their minute size, duckweeds exhibit distinction as per morpho-anatomical characterisation and production of secondary metabolites, that show antimicrobial potentialities. Connective stalk of duckweeds is an organ of attachment between the mother and daughter fronds, whose anatomy has been studied here in details. The present study focuses on the critical anatomical differences between Lemna minor L. and Spirodela polyrrhiza (L.) Schleid. using scanning electron microscope. The antimicrobial potency especially against Gram-negative bacteria were studied using duckweeds biomass collected from Indian aquatic environment, which were cultured in laboratory conditions. Activity against fish pathogen like Aeromonas sp. were investigated also. Bangladesh J. Bot. 52(1): 105-110, 2023 (March)